Endophytic Fusarium spp. from Roots of Lawn Grass (Axonopus compressus) - Latiffah Zakaria,; Chua Harn Ning, (Tropical Life Sciences Research, 2013)
Fungal endophytes are found inside host plants but do not produce any noticeable disease symptoms in their host. In the present study, endophytic Fusarium species were isolated from roots of lawn grass (Axonopus compressus). A total of 51 isolates were recovered from 100 root segments. Two Fusarium species, F. oxysporum (53%) and F. solani (47%), were identified based on macroconidia and conidiogenous cell morphology. The detection of endophytic F. oxysporum and F. solani in the roots of lawn grass contributes to the knowledge of both the distribution of the two Fusarium species and the importance of roots as endophytic niches for Fusarium species. Kulat endofit ditemui di dalam tumbuhan perumah tetapi tidak menunjukkan sebarang tanda-tanda yang ketara. Dalam kajian ini, spesies Fusarium endofitik telah dipencilkan daripada akar rumput halaman (Axonopus compressus) dan sebanyak 51 pencilan telah diperolehi daripada 100 segmen akar. Berdasarkan ciri-ciri morfologi bentuk makrokonidia dan sel conidiogenus, dua spesies Fusarium telah dikenalpasti iaitu, F. oxysporum (53%) dan F. solani (47%). Kehadiran F. oxysporum dan F. solani endofitik di dalam akar rumput halaman menyumbang kepada pengetahuan mengenai taburan kedua-dua spesies Fusarium dan kepentingan akar sebagai nic endofitik spesies Fusarium.